Nylon Intermediates from Bio‐Based Levulinic Acid - Marckwordt, Annemarie; El Ouahabi, Fatima; Amani, Hadis; Tin, Sergey; Kalevaru, Narayana V.; Kamer, Paul C. J.; Wohlrab, Sebastian; de Vries, Johannes G. (Angewandte Chemie International Edition, 2019)
Use of ZrO2/SiO2 as a solid acid catalyst in the ring‐opening of biobased γ‐valerolactone with methanol in the gas phase leads to mixtures of methyl 2‐, 3‐, and 4‐pentenoate (MP) in over 95 % selectivity, containing a surprising 81 % of M4P. This process allows the application of a selective hydroformylation to this mixture to convert M4P into methyl 5‐formyl‐valerate (M5FV) with 90 % selectivity. The other isomers remain unreacted. Reductive amination of M5FV and ring‐closure to ϵ‐caprolactam in excellent yield had been reported before. The remaining mixture of 2‐ and 3‐MP was subjected to an isomerising methoxycarbonylation to dimethyl adipate in 91 % yield. Green nylon: Use of 25 % ZrO2/SiO2 as catalyst allows the gas‐phase ring‐opening of bio‐based γ‐valerolactone with methanol to a mixture of methyl pentenoates containing 81 % of the 4‐isomer, which could be selectively hydroformylated from the mixture to methyl 5‐formyl‐valerate, an intermediate for ϵ‐caprolactam. The remaining isomers were converted into dimethyl adipate.